Holocene interactions between marine nomads and their coastal landscape in the Strait of Magellan, southern Patagonia: Ichthyoarchaeological and isotopic evidence - Torres Elgueta, Jimena Andrea; Gonzalez, Karina; Santana-Sagredo, Francisca; Andrade Diaz, Claudia Daniela Yanett; San Roman Bontes, Manuel Julio; Harrod, Chris (My University, 2024)
Marked environmental changes occurred in the southern Patagonian archipelago during the middle and late Holocene, including increased variability in glacial coverage and marine productivity. Those changes likely impacted the lives of marine hunter gatherers and their exploitation of faunal resources. Here, we examine temporal trends in fishes captured during the mid- and late Holocene, including variation in stable isotope values (delta 13C and delta 15N) of the most commonly exploited taxa to explore potential changes in fishing strategies due to environmental and cultural causes. We examined fish remains from eight archaeological sites and cultural periods in the Strait of Magellan. The ichthyoarchaeological results indicate drastic changes in the assemblages of fishes captured, with demersal species dominating catches before 2700 cal. yr BP and a subsequent switch to coastal fishes associated with subtidal kelp forests afterwards until 500 cal yr BP, both in the Strait of Magellan and adjacent seas. Although limited by sample sizes, our isotopic data show little obvious variation in Eleginops maclovinus over the different periods. However, Patagonotothen sp. and Salilota australis displayed significant isotopic shifts during the Holocene, but followed distinct, taxon-specific trajectories. This suggests that responses to the late Holocene environmental changes differed between species. This study also contributes to the baseline ecological information prior to the impact of modern industrial fishing practices with data from native fishes that are important components in kelp forests (Macrocystis pyrifera) ecosystems of the sub-Antarctic region.
Keywords: prehistoric fisheries; prehistoric ecology; patagonia; ichthyoarchaeology; stable isotope analysis; subantarctic ecosystems